Cognitive performance before and after the onset of subjective cognitive decline in old age. Issue 2 (3rd May 2015) - Koppara, Alexander; Wagner, Michael; Lange, Carolin; Ernst, Annette; Wiese, Birgitt; König, Hans‐Helmut; Brettschneider, Christian; Riedel‐Heller, Steffi; Luppa, Melanie; Weyerer, Siegfried; Werle, Jochen; Bickel, Horst; et al.
Abstract: Background: Our objectives were (1) to test the association between the report of subjective cognitive decline (SCD) and prospective objective cognitive performance in high age individuals and (2) to study the course of longitudinal cognitive performance before and after the first report of SCD. Methods: Cognitively normal elderly participants of the German Study on Ageing, Cognition, and Dementia study (N = 2330) with SCD (subjective decline in memory with and without associated concerns) and without SCD at baseline were assessed over 8 years with regard to immediate and delayed verbal recall, verbal fluency, working memory, and global cognition. Baseline performance and cognitive trajectories were compared between groups. In addition, cognitive trajectories before and after the initial report of SCD (incident SCD) were modelled in those without SCD at baseline. Results: Baseline performance in the SCD group was lower and declined more steeply in immediate and delayed verbal recall than in the control group (no SCD at baseline). This effect was more pronounced in the SCD group with concerns. Incident SCD was preceded by decline in immediate and delayed memory and word fluency. Conclusions: SCD predicts future memory decline. Incident SCD is related to previous cognitive decline. The latter finding supports the concept of SCD indicating first subtle decline in cognitive performance that characterizes preclinical Alzheimer's disease.